X-Ray Diffraction Analysis of the Sintered Y-TZP-AI[2]O[3] Ceramics; IOP Conference Series: Materials Science and Engineering; Vol. 140 : Interdisciplinary Problems in Additive Technologies - Savchenko N. Nickolai; Sablina T. Tatiana; Sevostyanova I.; Pshenichnyy A. Artem; Buyakova S. P. Svetlana Petrovna; Kulkov S. N. Sergey Nikolaevich (2016, 2016)
Title screen